DETERMINATION AND ANALYSIS OF THE PRICE/ EARNING INDICATOR VALUES’ INTERDEPENDENCE AT THE BEGINNING OF THE PERIOD AND WITH THE FORECASTED GROWTH (CHANGE) OF THE COMPANY’S ANNUAL PROFIT - O. Zemlyanskii (Вестник университета, 2019)
The dependence has been revealed, the calculation method and the formula of the price/ earning indicator values’ interdependence at the beginning of the period and with the forecasted annual company’s profit growth or change, – have been proposed. An analysis of the price/earning indicators’ dynamic in various economic situations has been given. The method of calculation has been offered and formulas of the required forecast growth of profit of the company for achievement of the necessary ratio price/earning of the companies have been defined. The formula for calculating and the analysis of the interdependence of growth or change in the value of the price/earning indicator and the projected annual growth of the company’s profit have been offered.